Lean Education: An Overview of Current Issues - Alves, Anabela Carvalho; Flumerfelt, Shannon; Kahlen, Franz-Josef (Springer International Publishing : Imprint: Springer, 2017)
This edited volume presents a structured approach to a new lean education curriculum, implemented for the education of engineers, managers, administrators as well as human resources developers. The authorship comprises professors and lecturers, trainers and practitioners who educate future professionals in Lean Thinking principles and tools. This edited book provides a platform for authors to share their efforts in building a Body of Knowledge (BoK) for Lean Education. The topical spectrum is state-of-the-art in this field, but the book also includes a glimpse into future developments. This is a highly informative and carefully presented book, providing valuable insight for scholars with an interest in Lean Education.